Transcription Factor RUNX3 Mediates Plasticity of ThGM Cells Toward Th1 Phenotype - Rasouli, Javad; Casella, Giacomo; Zhang, Weifeng; Xiao, Dan; Kumar, Gaurav; Fortina, Paolo; Zhang, Guang-Xian; Ciric, Bogoljub; Rostami, Abdolmohamad (Frontiers in Immunology, 2022)
GM-CSF-producing T helper (Th) cells play a crucial role in the pathogenesis of autoimmune diseases such as multiple sclerosis (MS). Recent studies have identified a distinct population of GM-CSF-producing Th cells, named ThGM cells, that also express cytokines TNF, IL-2, and IL-3, but lack expression of master transcription factors (TF) and signature cytokines of commonly recognized Th cell lineages. ThGM cells are highly encephalitogenic in a mouse model of MS, experimental autoimmune encephalomyelitis (EAE). Similar to Th17 cells, in response to IL-12, ThGM cells upregulate expression of T-bet and IFN- and switch their phenotype to Th1. Here we show that in addition to T-bet, TF RUNX3 also contributes to the Th1 switch of ThGM cells. T-bet-deficient ThGM cells in the CNS of mice with EAE had low expression of RUNX3, and knockdown of RUNX3 expression in ThGM cells abrogated the Th1-inducing effect of IL-12. Comparison of ThGM and Th1 cell transcriptomes showed that ThGM cells expressed a set of TFs known to inhibit the development of other Th lineages. Lack of expression of lineage-specific cytokines and TFs by ThGM cells, together with expression of TFs that inhibit the development of other Th lineages, suggests that ThGM cells are a non-polarized subset of Th cells with lineage characteristics.